ANALISIS BREAK EVEN POINT USAHA PETERNAKAN AYAM RAS PETELUR â€œUD. TETEY PERMAIâ€ DI KECAMATAN DIMEMBE - Winowoda, Beiyana; Salendu, A H.S; Manese, M A.V; Umboh, S. J.K (ZOOTEC, 2020)
ANALYSIS BREAK EVEN POINTÂ  OF LAYING CHICKEN LIVESTOCK BUSSINESS "UD TETEY PERMAI" IN KECAMATAN DIMEMBE. The purpose of this study was to analyze the Break even point of laying chicken breeding business "UD Tetey Permai." This research was conducted at the laying chicken breeding business "UD. Tetey Permai" in Dimembe District in July 2018 to August 2018. The data taken are primary data and secondary data. Primer data was obtained directly from company owners, company managers, cage workers and feed warehouse workers. Secondary data wasÂ  obtained through government agencies related to research.Â  The results showed that the laying chicken breeding business "UD. Tetey Permai" in one production period had a profit of Â Rp3.117.715.583 and had operated above Â Break Even Point on 1.129.389 eggs sales or on sales of Rp1.694.083.907.Â